Strength criterion and temperature dependent strength model of metallic glasses. (15th May 2019) - Zhang, Xianhe; Li, Weiguo; Deng, Yong; Shao, Jiaxing; Zhang, Xuyao; Chen, Liming
Highlights: A new strength criterion is proposed for BMGs for the whole range of stress states. A temperature dependent compressive strength model is established for BMGs. The tension-compression asymmetry can be characterized well by the new criterion. The temperature dependent tensile fracture angle can be explained by the new criterion. Abstract: In this paper, the different fracture mechanisms of bulk metallic glasses in tension and compression are investigated through combining its macroscopic fracture behaviors and unique atomic structure. It is found that the compressive fracture process of metallic glasses should be mainly controlled by the shear progress. In addition, both local shear process and local quasi-cleavage will happen under tensile loading due to the normal stress. Based on the analysis, a new strength criterion is proposed for metallic glasses from the viewpoint of energy, which is suitable for the whole range of stress states. The proposed criterion can give a good description of the experiment data of Zr-based metallic glasses in a wide normal stress range. Moreover, a temperature dependent compressive strength model is established based on the temperature dependent shear modulus model and the proposed strength criterion. The temperature dependence of tensile fracture angle can also be explained reasonably by the new criterion.